Using Recombinase-Aid Amplification Combined with Pyrococcus furiosus Argonaute for Rapid Sex Identification in Flamingo (Phoenicopteridae) - Shenluan Tan; Fanwen Zeng; Wanhuan Zhong; Tanzipeng Chen; Xuanjiao Chen; Li Li; Hengxi Wei; Shouquan Zhang (Animals)
Flamingos (Phoenicopteridae) are among the oldest birds worldwide and are loved by people for their bright red feathers. In addition, flamingos are sexually monomorphic birds, and distinguishing between males and females is difficult. The polymerase chain reaction (PCR) is widely used for sex identification. However, the PCR method requires a precise thermal cycler in the laboratory and is time-consuming. Therefore, developing a rapid, sensitive, and accurate method to identify the sex of flamingos is crucial. In this study, we established a sex identification system using a recombinase-aided amplification-Pyrococcus furiosus Argonaute (RAA-PfAgo) technique for greater flamingo (Phoenicopterus roseus). The greater flamingo-RAA-PfAgo system can identify unknown-sex greater flamingos in less than 1 h and can be visualized using a fluorescent detector or blue light. The results showed that optimal RAA-PfAgo conditions could detect 0.6 ng of genomic DNA and effectively differentiate between males and females. Random sample evaluations revealed that the system had a 100% coincidence rate compared with conventional PCR. In conclusion, this study provides a sensitive, specific, and accurate reference method for greater flamingo sexing.